PENJARINGAN DAN EDUKASI BAGI IBU HAMIL RISIKO TINGGI DI KECAMATAN KERENG BANGKIRAI - Lola Meyasa; Seri Wahyuni (Universitas Pahlawan Tuanku Tambusai, 2022)
Every pregnant woman is at risk of complications during her pregnancy and childbirth. The existence of physical and psychological health problems for pregnant women will have an impact on the quality of life of pregnant women as a whole, and can even increase the risk during pregnancy. In antenatal care, it is estimated that around 20% of pregnant women served by midwives at the puskesmas are classified as high-risk cases. Kereng Bangkirai Health Center is one of the health centers located on suburbs of Palangka Raya with the highest handling of obstetric complications, namely 45 people (47.5%). Through early detection, health promotion efforts in the form of health education and monitoring of pregnancy risk factors, as well as adequate treatment by health workers and health facilities, the incidence of complications during pregnancy and childbirth can be prevented or minimized. Screening and education of high-risk pregnant women in the working area of ??the Kereng Bangkirai Health Center is carried out well and smoothly. Of the 19 pregnant women who came, 10 (52.63%) pregnant women had risk factors in their pregnancy. Screening and education activities during home visits include pregnancy checks and Hb levels, delivery of education and evaluation (pre and post test). From the evaluation of the pre and post tests, it was found that there was an increase in knowledge of 40% during the pre test to 80% during the post test. All high-risk pregnant women who were accompanied during community service activities (100%) gave birth at health workers (midwifery independent practice/PMB). Keywords: screening, education, pregnant women at risk